Embolized conduits of rice (Oryza sativa, Poaceae) refill despite negative xylem pressure - Stiller, Volker; Sperry, John S.; Lafitte, Renee (Wiley, 2005)
Embolism reversal in rice plants was studied by testing the plant's ability to refill embolized conduits while xylem pressures were substantially negative. Intact, potted plants were water‐stressed to a xylem pressure of −1.88 ± 0.1 MPa and a 66.3 ± 3.8% loss of xylem conductivity (PLC) by cavitation. Stressed plants were carefully rewatered, allowing xylem pressure to rise, but not above the theoretical threshold of c. −0.15 MPa for embolism collapse. Despite xylem pressures being more negative than this threshold, the PLC fell significantly (28.5 ± 5.6%), indicating the refilling of vessels. Above c. −1.0 MPa, almost all plants regained their maximum hydraulic conductivity. Dye uptake experiments showed the same pattern of embolism refilling despite negative pressure. Refilling was prevented in plants that were light‐starved for 5 d, suggesting the unknown mechanism is dependent on metabolic energy. Results are among the first showing that herbaceous plants can reverse embolism without bulk xylem pressures rising near or above atmospheric.